Mudança organizacional e cultura organizacional : o caso da cooperativa agroindustrial C.Vale - Sanita, Anderson (2015)
Recent research has explored and demonstrated that there are still gaps in the academic and organizational level on organizational change and organizational culture. In order to clarify the understanding of how organizations deploy changes across their cultural characteristics, several studies have pointed to a promising path. This research aimed to characterize, from the current perspective of managers of an agribusiness cooperative, organizational changes and identify aspects related to organizational culture. The research method employed was the single case study, exploratory, with qualitative approach and design of historical and longitudinal survey. Data were collected from document analysis and semi-structured interviews. Data analysis was carried out using the technique of content analysis and triangulation. The collected data and the analysis of these data it was possible to identify and characterize two episodes of organizational change. The identification and characterization of these changes came from the observation of the presence of organizational change attributes mentioned in the literature.Also, the survey enabled the analysis of the perception of managers on organizational culture in organizational change. The description of these perceptions came from the observation of the presence of the attributes of organizational culture in the literature. It was possible to understand that episodes of organizational change, agro-industrialization and poultry activities as well as the perceptions of current managers about the organizational culture in the implemented changes, the dominance by the leaders of the group Culture Development, focusing on values like flexibility, growth and innovation, and by the Managers and Technicians groups predominate Hierarchical Culture, focusing on valuessuch as teamwork, participation and concern for ideas. The results also allowed an approach to the study so that it is possible to identify and characterize the organizational change and describe the perception of managers on organizational culture, strengthening the proposals from previous studies and indicating paths for future research on this topic.